Analysis of duodenal ulcer mortality trends by sex, race, age, and region in the United States, 1999–2023 - Ming-Jie Jia; Bo-Ying Wu; Feng Jiang (Medicine, 2026)
To systematically evaluate long-term trends in duodenal ulcer (DU)-related mortality in the United States (US) from 1999 to 2023 using US Centers for Disease Control and Prevention, Wide-ranging Online Data for Epidemiologic Research mortality registry data and to identify disparities by sex, race/ethnicity, age, region, and urban–rural setting, a retrospective population-based study design was employed. DU-related deaths were identified using International Classification of Diseases, 10th Revision code K26. Annual death counts were extracted, and age-adjusted mortality rates were calculated using the 2000 US standard population. Joinpoint regression (with Monte Carlo permutation testing) estimated annual percentage changes (APCs) and average APCs, reporting 95% confidence intervals. From 1999 to 2023, a total of 34,520 cumulative DU-related deaths occurred in the US The overall age-adjusted mortality rate declined from 0.83 to 0.64 per 100,000 (average APC = −1.32; 95% confidence interval = −2.75–0.14), with a marked decrease through 2009 followed by flattening and signs of resurgence thereafter. This “decline-then-rise” pattern was most evident among men, older adults (≥ 65 years), several racial and ethnic groups (including non-Hispanic White, Hispanic, and other races), and across all 4 census regions, while nonmetropolitan areas consistently had higher age-adjusted mortality rates than metropolitan areas. State-level analyses showed generally declining mortality with recent rebounds in several states. Over the past 2 decades, DU-related mortality in the US has generally declined. However, the rate of decline slowed around 2010, with rebounds occurring in certain populations. Persistent inequalities persist across sex, race/ethnicity, geographic regions, and urban/rural settings. Future public health strategies should implement stratified, targeted interventions for elderly and high-risk medication populations to reduce disparities and address emerging challenges.